Conformational polymorphism in racemic 2,4-Di-o-Benzoyl-6-o-Tosyl myo-Inositol 1,3,5-Orthoacetate - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Journal of Structural Chemistry, 2010)
The title compound, C(29)H(26)O(10)S, yields two conformational polymorphs concomitantly from dichloromethane-methanol mixture; the major polymorph grows as plates (Form I, monoclinic, P2(1)/n) and the minor polymorph grows as needles (Form II, triclinic, P-1). The two forms differ mainly in orientation of the tosyl group. In Form I, sulfonyl oxygen of the tosyl group makes intermolecular C -HaEuro broken vertical bar O interactions, whereas the same group in Form II is involved in an intramolecular short dipolar S=OaEuro broken vertical bar C=O (sulfonyl-carbonyl) contact. The molecular organization and the influence of various weak non-covalent interactions that stabilize these conformers in the crystal lattices are discussed.
Keywords: Conformation; crystal structure; dipolar interactions; Inositol; non-covalent interactions; polymorphism; sulfonyl-carbonyl contact

Alternating electric-field-induced assembly of binary mixtures of soft repulsive ionic microgel colloids - Jathavedan, Kiran; Bhat, Suresh K.; Mohanty, Priti S. (Journal of Colloid and Interface Science, 2019)
An external alternating electric field is used to study the assembly of a binary mixture of Poly(N-isopro pylacrylamide-co-acrylic acid) microgels in their swollen form at hydrodynamic size ratio 2:1 under deprotonated state. The AC field experiments were carried out at a fixed frequency of 100 kHz in the fluid regime for three number density ratios 1:3, 1:1 and 3:1 of big-to-small microgels using a confocal microscope. Strings with different types of co-assembly structures such as buckled, ring, flame and sandwich have been observed at low and intermediate field strengths at ratio 1:3, 1:1. In buckled and ring type, one or two small particles sit at the contact of two big particles and in the flame type, small particles arrange like a cone at end of the string. In the sandwich structure, several double small particle layers lie in between big particles. At high field strength, aggregation of strings and a phase separation into individual aggregates of strings from both big and small microgels have been observed. At higher ratio 3:1, the string formation is mostly dominated by big particles. Our experimental results are discussed with the recent simulation and experimental works on AC field induced structures in binary hard sphere mixtures. (C) 2019 Elsevier Inc. All rights reserved.
Keywords: assembly; dipolar interactions; Microgels; Soft colloids